Word toys : poetry and technics - Stefans, Brian Kim (Book collections on Project MUSE., 2017)
An engaging and thought provoking volume that speculates on a range of textual works-poetic, novelistic, and programmed-as technical objects With the ascent of digital culture, new forms of literature and literary production are thriving that include multimedia, networked, conceptual, and other as-yet-unnamed genres while traditional genres and media-the lyric, the novel, the book-have been transformed. Word Toys: Poetry and Technics is an engaging and thought-provoking volume that speculates on a range of poetic, novelistic, and programmed works that lie beyond the language of the literary and which views them instead as technical objects. Brian Kim Stefans considers the problems that arise when discussing these progressive texts in relation to more traditional print-based poetic texts. He questions the influence of game theory and digital humanities rhetoric on poetic production, and how non-digital works, such as contemporary works of lyric poetry, are influenced by the recent ubiquity of social media, the power of search engines, and the public perceptions of language in a time of nearly universal surveillance. Word Toys offers new readings of canonical avant-garde writers such as Ezra Pound and Charles Olson, major successors such as Charles Bernstein, Alice Notley, and Wanda Coleman, mixed-genre artists including Caroline Bergvall, Tan Lin, and William Poundstone, and lyric poets such as Harryette Mullen and Ben Lerner. Writers that trouble the poetry/science divide such as Christian Bök, and novelists who have embraced digital technology such as Mark Z. Danielewski and the elusive Toadex Hobogrammathon, anchor reflections on the nature of creativity in a world where authors collaborate, even if unwittingly, with machines and networks. In addition, Stefans names provocative new genres-among them the nearly formless "undigest" and the transpacific "miscegenated script"-arguing by example that interdisciplinary discourse is crucial to the development of scholarship about experimental work.